Vehicle Routing and Scheduling Problem for a multi-period, multi-perishable product system with time window: A Case study - Alireza Rashidi Komijan; Danial Delavari (International Journal of Production Management and Engineering)
The well-known Vehicle Routing Problem (VRP) is to find proper sequence of routes in order to minimize transportation costs. In this paper, a mixed-integer programming model is presented for a food distributer company and the model outputs are to determine the optimal routes and amount of pickup and delivery. In the objective function, the costs of transportation, holding, tardiness and earliness are considered simultaneously. The proposed model with respect to real conditions is multi-period and has two different time periods: one for dispatching vehicles to customers and suppliers and the other for receiving  customers’ orders. Time window and split pickup and delivery are considered for perishable products. The proposed model is  nonlinear and will be linearized using exact techniques. At the end, model is solved using GAMS and the sensitivity analysis  is performed. The results indicate that the trend of changes in holding and transportation costs in compared to tardiness and  earliness costs are closed together and are not so sensitive to demand changes.